SEAPOWER AND ASYMMETRIC WARFARE IN INDONESIA - Primayanti, Luh Putu Ika; Putra, Saudi Firmansyah (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2020)
This study analyzes the Asymmetric Warfare that occurs at sea and the seapower that should be possessed by a state to overcome maritime asymmetrical threats. This study uses descriptive qualitative which explains in detail the asymmetrical warfare at sea and seapower using case examples. This research uses case examples of asymmetrical threats that occur in the domestic territory of Indonesia, namely the Malacca Strait case. The theories used in this study are defense theory, the concept of seapower, the concept of asymmetric warfare and the concept of international cooperation to analyze the case that occurs. The results of this study are Indonesia’s seapower to combat asymmetric warfare was built in three ways namely, strengthen the military defense equipment, carry out defense cooperation with the state that borders with Indonesia and strengthen the collaboration between related ministries and institutions. These ways are implemented through Malacca Strait Patrol which is defense cooperative include Malacca Sea Strait Patrol, Eyes in the Sky and Information Sharing.